Policies and practices for teaching sociocultural diversity : report on the survey on initial education of teachers in sociocultural diversity - Arnesen, Anne-Lise, 1943- (Councile of Europe, 2008)
"Although teaching and management of diversity are taken into account in almost all the countries participating in the survey, the 'enhanced value' of diversity, which implies the creation of conditions for inclusive participation favorable to equal opportunities for all, is not unanimously approved. This report underlines that teacher education institutions play an important role, in collaboration with policy makers, in drafting study programs, but also in defining national policies concerning teacher education. Such is not always the case for the relevant qualification requirements for teachers, the evaluation of associated skills or the recognition of experience gained in the field of sociocultural diversity. This report is the result of a survey on the initial training of teachers in sociocultural diversity in Europe, carried out in 16 countries within the framework of the project 'Policies and practices for teaching sociocultural diversity' launched by the Steering Committee for Education of the Council of Europe in 2006. An analysis of replies from practitioners completes the results of the survey. The recommendations contained in this report will serve as a basis for carrying out the second phase of the project on the definition of a framework of teachers competences relating to the enhanced value of diversity."--Resumé vydavatele
Vydáno též francouzsky pod názvem: Politiques et pratiques de l'enseignement de la diversité socioculturelle : rapport de l'enquête sur la formation initiale des enseignants à la diversité socioculturelle
Keywords: vzdělávání učitelů -- země Evropské unie; pluralismus -- země Evropské unie; kulturní diverzita -- země Evropské unie; multikulturalismus -- země Evropské unie; multikulturní výchova -- země Evropské unie; teacher education -- European union countries; pluralism -- European union countries; cultural diversity -- European union countries; multiculturalism -- European union countries; multicultural education -- European union countries; sociokulturní diverzita; výzkumné zprávy; research reports